Communiversity initiative via knowledge transfer project (KTP-RIGS): Realising the meaning of Rahmatan Lil-Alamin to disabled community through modern agriculture - Yunus, Muhamad Fahmi; Salleh, Mohd Syahmi; Ponari, Md Hoirul Azri; Shahari, Rozilawati; Muhamad Tajudin, Nur Shuhada; Karim, Mohd Fauzihan; Mohd Yunus, Noor Syaheera (IIUM Press, 2024)
This project explores the transformative role of the Communiversity initiative under the Knowledge Transfer Project (KTP-RIGS) IIUM in empowering the disabled community through modern agriculture. Rooted in the Islamic concept of Rahmatan lil-Alamin (Mercy to all creation), the project seeks to bridge the gap between academic knowledge and societal needs, fostering inclusivity and sustainability. By equipping disabled individuals with agricultural skills and modern farming techniques, the initiative exemplifies how community-based learning can uplift marginalized groups. The aim of this project is to improve self-reliance and quality of life of the disabled trainees at Pertubuhan Pemulihan Dalam Komuniti Kompleks Penyayang (PDK), Jabatan Kebajikan Masyarakat (JKM), Kuantan, Pahang, while at the same time promoting food security in Malaysia. The main activities conducted for this programme were fertigation and hydroponic training for the disabled trainees where they were trained based on their own capacity and capability. Additionally, herbs garden was also established at the PDK training centre with the involvement of parents and family members of the disabled trainees.